Dispute avoidance procedure: formulating a workable legal system in the Malaysian construction industry - Mohd Danuri, Mohd Suhaimi; Mohd Ishan, Zahira; Mustaffa, Nur Emma; Abd Karim, Saipol Bari; Mohamed, Othman; Hanid, Mahanim (Faculty of Built Environment, University of Malaya, 2016)
Research on dispute avoidance procedure (DAP) particularly in Malaysia is lacking as most of the current research and development deals with various issues within the dispute resolution procedure and management field. It is therefore significant to conduct a country-specific research by exploring the viability of DAP based on socio-legal research. The aim of this article is two-fold: to present the perceptions of the Malaysian construction industry players on the substantive elements of a viable DAP mechanism and; to formulate a necessary legal reform to accommodate and support the formulated DAP mechanism within the Malaysian construction industry. As part of a socio-legal research approach, interviews were conducted with the selected construction industry players to disclose the pattern, which may help to explain the underlying issues. NVivo software has been used to manage and organize the complete interview transcripts and facilitate the data analysis process for this study. Among others, this research suggests that a viable DAP mechanism consists of the following substantive elements, namely, to introduce the mechanism through contract and to provide a contractually binding settlement. In essence, this research also advocates a necessary legal reform to accommodate and support the formulated DAP mechanism within the Malaysian construction industry. This research generally confirms that a country-specific research is required through a socio-legal research.